Faktor – Faktor yang Mempengaruhi Penerimaan Opini Audit Going Concern ( Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI 2008-2010) (Students' Journal of Accounting and Banking, 2012)
This study aims to examine the effect of company size, audit quality, and audit opinions the previous year. The population used in this study are all manufacturing companies listed in Bursa Efek Indonesia (BEI). The samples obtained by using purposive sampling method have a problem with financial distress criteria, the accumulated losess, eraning’s negative, current operations and net income is negative.Hypothesis testing is done by multivariate analysis using logistic regression the independent variable is a combination of metric and non metric (nominal). This analysis technique does not require normality test and test again the assumption on the independent variables. Logistic regression models, asses model fit, and parameter estimation and interpretation.In this study, quality audit and the audit opinion the previous year has positive influence on the possibility of receiving going concern audit opinion. While the size of the company’s revenues negatively affect the possibility og receiving going concern audit opinion.Keywords: Size Of The Company, Quality Auditor, The Previous Year’s Opinion, Going Concern.